2013
DOI: 10.1093/bja/aet104
|View full text |Cite
|
Sign up to set email alerts
|

Recovery after total intravenous general anaesthesia or spinal anaesthesia for total knee arthroplasty: a randomized trial

Abstract: GA had more favourable recovery effects after TKA compared with SA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(62 citation statements)
references
References 21 publications
(36 reference statements)
3
57
0
1
Order By: Relevance
“…However, the NRS scores at the 24 th hour were significantly higher. As in this study, Harsten et al observed that during the first 2 hours after general anaesthesia, patients had higher pain scores, but after 6 hours the spinal group had significantly higher pain scores [33]. This finding may be due to the pain perception of the patients; during the first postoperative hours the analgesic action of spinal anaesthesia continues and the patients are pain free.…”
Section: Discussionsupporting
confidence: 54%
“…However, the NRS scores at the 24 th hour were significantly higher. As in this study, Harsten et al observed that during the first 2 hours after general anaesthesia, patients had higher pain scores, but after 6 hours the spinal group had significantly higher pain scores [33]. This finding may be due to the pain perception of the patients; during the first postoperative hours the analgesic action of spinal anaesthesia continues and the patients are pain free.…”
Section: Discussionsupporting
confidence: 54%
“…[12] As opioids alone are not sufficient for an adequate analgesia, a multimodal analgesic approach has been accepted recently. [3] Analgesic benefits of peripheral nerve blocks are well described.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate analgesia is essential after total knee arthroplasty (TKA)[12] to improve postoperative mobilization and reduce the length of hospital stay (LOS). It is difficult to achieve good analgesia only with opioids, even when combined with nonsteroidal anti-inflammatory drugs.…”
Section: Introductionmentioning
confidence: 99%
“…We also found anesthesia and its administration to have a role in LOS: THA patients who underwent general, endotracheal anesthesia were associated with a longer LOS than THA patients who had spinal, regional anesthesia. This factor does not seem to be widely reported in the existing literature, though Harsten et al found that subjects receiving general anesthesia had a shorter LOS and their patients preferred receiving general anesthesia if they had to redo their surgery [24]. This may require further research with a study of higher power and more focus on the anesthesiology side of perioperative care, particularly as to its role in the JSH.…”
Section: Discussionmentioning
confidence: 99%
“…The existing literature points to the fact that these operations should be best conducted in tertiary-care institutions, with early and thorough patient education, early and consistent physical therapy, and individual planning to minimize LOS [10, 11, 20, 21, 23, 25, 27]. Other factors that have a dramatic impact are management of depression and anxiety and the importance of appropriate pain management in decreasing LOS [12, 24]. Further research into anesthesia (in relation to pain management, ASA score, and operative anesthesia administration) should be conducted to improve this pathway.…”
Section: Discussionmentioning
confidence: 99%